Unit Cost Analysis for Cost Planning and Control in Non-Formal Education: A Case Study of Muhammadiyah Guidance Center (SBM) Kepong, Malaysia (2024-2025) - Nur Syanif Yusuf Habib Rizki; Evi Dwi Kartikasari (Universitas Bhayangkara Surabaya, 2026)
Education financing management is crucial for the sustainability of non-formal educational institutions with limited funding sources. This study analyzes unit cost calculation as a basis for planning and controlling education costs at the Muhammadiyah Guidance Center (SBM) Kepong in Kuala Lumpur, Malaysia, which serves children of Indonesian Migrant Workers. Using a qualitative case study approach, data were collected through interviews, observation, and document analysis. The findings reveal that monthly operational costs range from RM5.000 to RM6.000 for approximately 60 students, resulting in a unit cost of RM83-RM100 per student. The tuition fee of RM120 provides a buffer against unexpected expenses and payment arrears. This demonstrates that unit cost analysis is a vital instrument for budget planning, cost control, and institutional sustainability. The study recommends strengthening financial recording and diversifying funding sources to enhance accountability and efficiency.